2009
DOI: 10.1103/physrevb.79.085301
|View full text |Cite
|
Sign up to set email alerts
|

Energy level spectroscopy of InSb quantum wells using quantum-well LED emission

Abstract: We have investigated the low-temperature optical properties of InSb quantum-well ͑QW͒ light-emitting diodes, with different barrier compositions, as a function of well width. Three devices were studied: QW1 had a 20 nm undoped InSb quantum well with a barrier composition of Al 0.143 In 0.857 Sb, QW2 had a 40 nm undoped InSb well with a barrier composition of Al 0.077 In 0.923 Sb, and QW3 had a 100 nm undoped InSb well with a barrier composition of Al 0.025 In 0.975 Sb. For QW1, the signature of two transitions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Transmission electron microscopy (TEM) analyses showed that microtwins (MTs) and threading dislocations (TDs) are dominant structural defects in InSb QWs grown on GaAs(001) substrates, [2][3][4] which are common choices of substrates for InSb-QW-based devices. [5][6][7][8][9][10][11] These defects degrade the total electron mobilities in InSb QWs. 4,12,13) Based on regression analyses for Matthiessen's law, recently we have reported quantitative studies for electron scattering due to both TD and MT defects in InSb QWs, 12,13) although the effect of these defects on electron transport in InSb epilayers [14][15][16][17][18][19] and non-InSb two-dimensional (2D) systems [20][21][22][23][24][25] which include QW structures has long been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Transmission electron microscopy (TEM) analyses showed that microtwins (MTs) and threading dislocations (TDs) are dominant structural defects in InSb QWs grown on GaAs(001) substrates, [2][3][4] which are common choices of substrates for InSb-QW-based devices. [5][6][7][8][9][10][11] These defects degrade the total electron mobilities in InSb QWs. 4,12,13) Based on regression analyses for Matthiessen's law, recently we have reported quantitative studies for electron scattering due to both TD and MT defects in InSb QWs, 12,13) although the effect of these defects on electron transport in InSb epilayers [14][15][16][17][18][19] and non-InSb two-dimensional (2D) systems [20][21][22][23][24][25] which include QW structures has long been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously obtained estimated values of the effective carrier temperature in the QWLEDs, at low temperature and under net bias, of 105 K and 129 K for QW2 and QW3, respectively, 17 corresponding to carrier energies of approximately 10 meV. In comparison, the energy difference between the lowest electron subband and the barrier conduction band is approximately 20 meV and 45 meV for QW2 and QW3, respectively (at low temperature under net bias).…”
mentioning
confidence: 99%
“…The bandstructure of the devices (calculated using an eight-band kÁp model) can be found in Ref. 17. The very small electron effective mass ($0.014 m o ) in InSb, approximately one fifth that in GaAs, leads to strong quantum confinement even in relatively wide quantum wells.…”
mentioning
confidence: 99%
See 2 more Smart Citations